Rancang Bangun Algoritma Kalkulus untuk Mengkalkulasi Efisiensi Konversi pada Modul Daya - Irvan Malay; Tegar Ramadhan; Khairul; Muhammad Rachmat; Tuahman Turnip (Jurnal Sains Dan Teknologi | E-ISSN : 3063-9980, 2026)
This study presents a Calculus-based framework for calculating conversion efficiency in power electronics modules, with emphasis on the integration of MATLAB/Simulink for modeling and validation. The main objective is to formulate the dynamics of efficiency using differential calculus, and to optimize conduction paths and converter topology through vector calculus and variational calculus. The methodology includes mathematical modeling based on differential equations to capture conversion dynamics, transient analysis via signal processing, and optimization algorithms grounded in calculus of variations to minimize conduction losses, switching losses, and thermal losses. Validation is performed through numerical simulations in MATLAB/Simulink and experimental testing on DC-DC converter and inverter prototypes under diverse loading and temperature conditions. Initial results indicate that the calculus-based approach enhances the accuracy of efficiency estimation and provides clearer insights into the trade-offs between converter topology and operational load. The study concludes by highlighting the potential of calculus-based techniques for designing more efficient power modules and offering recommendations for topology exploration and parameter optimization under varying thermal environments. Keywords: calculus, algorithms, MATLAB, Simulink, efficiency, power module, DC-DC converter, vector calculus, transient analysis.